PENGARUH LOYALITAS MEREK, PENGALAMAN PENGGUNA DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN PREMIUM CURRENCY PADA PERMAINAN ONLINE BERBASIS MOBILE - Putra, I Gede Wisnu Satria Chandra; Natalia, Desy (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2023)
This research was conducted to analyze the factors that influence purchasing decisions for premium currency in mobile-based online games that are currently popular in Indonesia. In this case the author makes the online game Mobile Legends and Genshin Impact the object of research. This research was conducted using statistical testing methods on data from questionnaires that were successfully collected from 109 respondents. As a result, brand loyalty, user experience and sales promotions all have a significant positive effect on the purchase decision of premium currency in mobile-based online games either simultaneously or partially. Brand loyalty has the most significant influence compared to other variables due to the strong loyalty of Mobile Legends and Genshin Impact players. While sales promotion chooses the lowest effect due to the lack of promotion from both publishers and influencers.